2023
DOI: 10.1101/2023.03.28.534543
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PRC domain-containing proteins modulate FtsZ-based archaeal cell division

Abstract: Dividing cells into two daughter cells is a complicated process that in bacteria and eukaryotes requires many proteins to work together. For archaea that divide via an FtsZ-based mechanism, only three proteins of the cell division machinery could so far be identified. These are two tubulin homologs, FtsZ1, FtsZ2 and the membrane anchor of FtsZ2, SepF. Here, we investigate additional archaeal cell division proteins that were identified by immunoprecipitation of SepF. These proteins comprise a single PRC-barrel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Two independent recent studies reported PRC barrel protein to be essential for cell division in Haloferax volcanii (51, 69). It has been shown that two PRC barrel proteins form a tripartite complex with SepF which recruits FtsZ to the divisosome (51, 69). It has been thought previously that Thermoproteales had a unique cell division apparatus because neither FtsZ nor ESCRT system genes were identified in these genomes (24).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two independent recent studies reported PRC barrel protein to be essential for cell division in Haloferax volcanii (51, 69). It has been shown that two PRC barrel proteins form a tripartite complex with SepF which recruits FtsZ to the divisosome (51, 69). It has been thought previously that Thermoproteales had a unique cell division apparatus because neither FtsZ nor ESCRT system genes were identified in these genomes (24).…”
Section: Resultsmentioning
confidence: 99%
“…During the recent decade, considerable progress has been reached in understanding the functionality of both FtsZ-based and ESCRT-based molecular machineries in archaea (68). Two independent recent studies reported PRC barrel protein to be essential for cell division in Haloferax volcanii (51, 69). It has been shown that two PRC barrel proteins form a tripartite complex with SepF which recruits FtsZ to the divisosome (51, 69).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CDS of FtsZ1-2 and FtsZ2-1 lacking the N-terminal transit peptides (86 and 42 amino acids, respectively) were amplified via PCR (Supplemental Table S4) and subcloned into the linearized pSVA13429 vector (Nußbaum et al, 2023) via Gibson cloning (Gibson et al, 2009). The final vectors were sequenced with SUMO_fwd and T7_rev (Supplemental Table S4).…”
Section: Methodsmentioning
confidence: 99%
“…Cleavage was performed overnight at 4 °C using 20 ng/mL His-Ulp1 protease (SUMO-protease) in the presence of 2 mM DTT, 0.1 % ND-40, 200 μM GDP, and 1 mM MgCl 2 . SUMO protease was produced in-house (Lau et al, 2018; Nußbaum et al, 2023). Following the removal of the His 6 _SUMO-tag, the pH was increased to pH 10 for FtsZ1-2, and kept at 9.5 for FtsZ2-1.…”
Section: Methodsmentioning
confidence: 99%